Computed tomography versus sleep endoscopy (DISE) to predict the effectiveness of mandibular advancement device in adult patients with obstructive sleep apnea: A systematic review - Pedro Cebola; Cristina Caroça; Helena Donato; Sara Dias; João Paço; Cristina Manso (PLoS ONE, 2025)
Study objectives Obstructive sleep apnea (OSA) has a high prevalence in the global population and is a significant sleep disorder. One of the non-invasive options to treat obstructive sleep apnea is the mandibular advancement device. 2 methods can help predict the success of mandibular advancement devices, and they are Neck computed tomography (CT) and Drug-induced Sleep endoscopy (DISE). The objective of this study was to determine which method is better at predicting the success of a mandibular advancement device in the treatment of obstructive sleep apnea. Methods PubMed, Embase and Web of Science Core Collection databases were comprehensively searched. A total of 1809 was obtained through the extensive search of the three databases mentioned above (Embase = 952; PubMed = 508; Web of Science = 349). The exclusion criteria were studies lacking clear and replicable methodologies; research involving pediatric and adolescent participants, as well as individuals with craniofacial malformations; and Animal studies, conference abstracts, editorials, case reports, book chapters, and review articles. Results Based on the inclusion criteria, mainly because of the lack of direct comparison between CT and DISE for the prediction of MAD success, two articles were selected for this systematic review. The conflicting findings between the two studies underscore the complexity of OSA management and challenges associated with predicting treatment outcomes using different diagnostic modalities. Conclusions Although CT offers detailed anatomical information regarding airway morphology, DISE provides dynamic visualization of upper airway collapse during sleep, which may better simulate real-life conditions and MAD responses.